1974
DOI: 10.1103/physrevlett.32.1231
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent Heating and Quenching of the Ion Sound Instability

Abstract: Turbulent heating and stabilization of the ion sound instability is investigated by twodimensional computer simulation. Quasilinear rather than nonlinear effects determine the evolution of the instability. The instability is quenched by flattening of the electron distribution and the formation of a high-energy ion tail.Numerous stabilization mechanisms have been proposed for the current-driven ion sound instability. 1 "* 5 We have done extensive simulation studies in order to provide a test for these basic pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
53
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(62 citation statements)
references
References 4 publications
9
53
0
Order By: Relevance
“…Electron VDFs measured by IES exhibit features that are consistent with previous electron acceleration studies (Thomsen et al 1986;Feldman et al 1983b;Hall et al 1986;Bingham et al 1988). Table 1 summarizes the values of p found in this study and previous Feldman et al (1983a) 4−7.5 Flat-topped distributions in interplanetary shocks Feldman et al (1983a) 3.6−4 Ion acoustic heating in laboratory studies Dum et al (1974) 2.5−13 Comet G-Z Thomsen et al (1986) 2−15 Comet 67P This study works. Here, we briefly introduce the various mechanisms that have been shown to accelerate electrons and discuss the context of our observations.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Electron VDFs measured by IES exhibit features that are consistent with previous electron acceleration studies (Thomsen et al 1986;Feldman et al 1983b;Hall et al 1986;Bingham et al 1988). Table 1 summarizes the values of p found in this study and previous Feldman et al (1983a) 4−7.5 Flat-topped distributions in interplanetary shocks Feldman et al (1983a) 3.6−4 Ion acoustic heating in laboratory studies Dum et al (1974) 2.5−13 Comet G-Z Thomsen et al (1986) 2−15 Comet 67P This study works. Here, we briefly introduce the various mechanisms that have been shown to accelerate electrons and discuss the context of our observations.…”
Section: Discussionsupporting
confidence: 88%
“…We therefore fit the suprathermal component of the electron distribution using (Thomsen et al 1986;Feldman et al 1983b,a;Dum et al 1974)…”
Section: Electron Observationsmentioning
confidence: 99%
“…Multi-dimensional computer simulations show that current-driven ion-acoustic turbulent spectrum is flared out within about 45 • of the current direction (Biskamp & Chodura 1971;Biskamp et al 1972;Dum et al 1974). The presence of a background magnetic field, as in solar flare systems, will likely inhibit scattering perpendicular to the field, making it less effective in suppressing the transport of hot electrons.…”
Section: Discussion and Applicationmentioning
confidence: 99%
“…When examining the investigations on the current-driven ion-acoustic instability, one can find that nearly all the works have employed the Maxwellian velocity distribution as the statistical description for the stationary distribution of the ions and electrons. However, computer simulations revealed that the electron distribution was not purely Maxwellian [1]. In some physical situations of either laboratory plasma or space plasma, the velocity distributions are not Maxwellian one but behave the power-law.…”
Section: Introductionmentioning
confidence: 99%